Progression to active tuberculosis, but not transmission, varies by M. tuberculosis lineage in The Gambia - de Jong, Bouke C. (2008)
Considerable variability exists in the outcome of M. tuberculosis infection. We hypothesized that M. africanum was less likely than M. tuberculosis to transmit and progress to tuberculosis disease. In a cohort study of tuberculosis patients and their household contacts in the Gambia, we categorized 1,808 HIV negative tuberculosis contacts according to exposure to M. tuberculosis or to M. africanum. A positive skin test indicated transmission and development of tuberculosis during 2 years of follow-up indicated progression to disease. Transmission was similar, but progression to disease was significantly lower in contacts exposed to M. africanum than to M. tuberculosis (1.0% vs 2.9%; Hazard Ratio (HR) 3.1, 95% CI 1.1–8.7). Within M. tuberculosis sensu stricto, contacts exposed to a Beijing family strain were most likely to progress to disease (5.6%; HR 6.7 (2.0–22) relative to M. africanum). M. africanum and M. tuberculosis transmit equally well to household contacts, but contacts exposed to M. africanum are less likely to progress to tuberculosis disease than those exposed to M. tuberculosis. The variable rate of progression by lineage suggests that TB variability matters in clinical settings and should be taken into account in studies evaluating tuberculosis vaccines and treatment regimens for latent tuberculosis infection.